Once NEET, Always NEET? A Synthetic Panel Approach to Analyze the Moroccan Labor Market - Alfani, Federica; Clementi, Fabio; Fabiani, Michele; Molini, Vasco; Valentini, Enzo (World Bank, Washington, DC, 2020)
In many regions of the world, the persistent, and growing, proportion of young people who are currently not in employment, education, or training is of global concern. This is no less true of Morocco: about 30 percent of the Moroccan population between ages 15 and 24 are currently not in employment, education, or training. Drawing from various rounds of Moroccan labor force surveys, this paper contributes to understanding the complex dynamics of labor markets in developing countries. First, it identifies the socioeconomic determinants of Morocco's young population not in employment, education, or training. Second, employing a synthetic panel methodology in the context of labor market analysis, the paper describes how the conditions of individuals in this group has changed over time. One striking, and worrisome, pattern that emerges from the 2010 synthetic panel data is that, even after 10 years, a majority of the young population not in employment, education, or training remained outside the labor market or education, with very little chance of moving out of their situation. Their chronic stagnancy confirms the powerful effect that initial conditions have on determining young people's future outcomes.